Pengolahan Limbah Pertanian Dalam Mendukung Zero Waste di Kawasan Desa Pakuan Kecamatan Narmada Kabupaten Lombok Barat - Guyup Mahardhian Dwi; Endang Purnama Dewi; Wenny Amaliah; Gagassage Nanaluih De Side; Diah Ajeng Setiawati; Windy Anindya Dwi Herdiana; Nurul Cahya Novianti Pertama (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2025)
This community engagement program was implemented in Pesantek Hamlet, Pakuan Village, Narmada District, West Lombok, in response to the suboptimal management of agricultural and household waste, particularly banana peels, which pose environmental and health risks. The primary objective was to enhance awareness, knowledge, and skills among local residents especially small business operators, farmers, and homemakers in processing organic waste into solid compost and liquid organic fertilizer (POF) with economic value. The program adopted a participatory approach involving technical training, educational outreach, hands on demonstrations, and sustained mentoring, utilizing a learning by doing strategy delivered to 20 participants. Evaluation was conducted using both qualitative and quantitative methods to assess changes in understanding and practical skills. Results showed that 90% of participants were able to independently produce fertilizer and apply sustainable waste management practices. Moreover, the initiative led to collective community actions for communal waste management, fostered environmentally based entrepreneurial opportunities, and generated a replicable educational model. This intervention contributes to the achievement of the Sustainable Development Goals (SDGs), particularly those related to responsible consumption and production as well as environmental conservation in rural settings.